Non-dipping pulse rate and chronic changes of the kidney in patients with chronic kidney disease - Oba, Rina; Kanzaki, Go; Haruhara, Kotaro; Sasaki, Takaya; Okabayashi, Yusuke; Koike, Kentaro; Tsuboi, Nobuo; Yokoo, Takashi (Frontiers in Cardiovascular Medicine, 2023)
Introduction An insufficient decrease in nocturnal pulse rate (PR), non-dipping PR, reflects autonomic imbalance and is associated with cardiovascular events and all-cause mortality. We aimed to investigate the clinical and microanatomical structural findings associated with the non-dipping PR status in patients with chronic kidney disease (CKD). Methods This cross-sectional study included 135 patients who underwent ambulatory blood pressure monitoring and kidney biopsy concurrently at our institution between 2016 and 2019. Non-dipping PR status was defined as (daytime PR-nighttime PR)/daytime PR <0.1. We compared clinical parameters and microstructural changes in the kidney between patients with and without non-dipping PR, including 24 h proteinuria, glomerular volume, and Mayo Clinic/Renal Pathology Society Chronicity Score. Results The median age was 51 years (interquartile range: 35–63), 54% of which were male, and the median estimated glomerular filtration rate was 53.0 (30.0–75.0) mL/min/1.73 m2. Non-dipping PR status was observed in 39 patients. Patients with non-dipping PR were older and had worse kidney function, higher blood pressure, greater prevalence of dyslipidemia, lower hemoglobin levels, and a larger amount of urinary protein excretion than patients with dipping PR. Patients with non-dipping PR had more severe glomerulosclerosis, interstitial fibrosis, tubular atrophy, and arteriosclerosis. In the multivariable analysis, the severe chronic changes of the kidney were associated with non-dipping PR status after adjusting for age, sex, and other clinical parameters (odds ratio = 20.8; 95% confidence interval, 2.82–153; P = 0.003). Conclusion This study is the first to indicate that non-dipping PR is significantly associated with chronic microanatomical changes in the kidneys of patients with CKD.